Resources and Constraints of the Work of Political Journalists in Information Enterprises - Caballero Rojas, Gerardo (2019)
This article describes how, in the current media context, political journalists who work in an informative company receive, on the one hand, material resources that help them to carry out their work but, on the other hand, they are subject to a series of constraints, which we have defined in two types: corporate constraints, which are related to the capitalist business nature of the media, editorial constraints, which are linked to political preferences or sympathies. To better understand these resources and constraints, we interviewed four journalists from the Politics section of a Peruvian  information company, who describe their work routines.